A new approach to measure the elasticity modulus for ceramics using the deformation energy method - Foschini, Cesar R. [UNESP] (2016)
This paper presents an alternative method to measure the modulus of elasticity to traction, E, for relatively limited sample sizes. We constructed a measurement system with a Force sensor (FS) and a Rotation movement sensor (RMS) to obtain a relationship between force (F) and bending (ΔL). It was possible by calculating the strain energy and the work of a constant force to establish a relationship between these quantities; the constant of proportionality in this relationship depends on E, I and L. I and L are the moment of inertia of the uniform cross-section in relation to an oriented axis and length, respectively, of the sample for bending. An expression that could achieve the value of E was deduced to study samples of Y-TZP ceramics. The advantages of this system compared to traditional systems are its low cost and practicality in determining E.